Short counseling techniques for busy family doctors. - Poon, V. H. (College of Family Physicians of Canada, 1997)
OBJECTIVE: To introduce two short counseling skills for busy family doctors: the BATHE technique and the DIG technique. QUALITY OF EVIDENCE: The BATHE technique indicates five areas for questioning patients who require counseling: background, affect, trouble, handling, and empathy. No research on use of the technique has been published. The DIG technique is the author's modification of the BATHE technique. MAIN FINDINGS: While the efficacy of counseling in general was validated, more research on the effectiveness on these two techniques needs to be done. CONCLUSIONS: Since counseling is an integral part of family practice, family doctors will find these techniques useful. Each is easy to learn and takes less than 15 minutes to complete.